Therapies for hidradenitis suppurativa: a systematic review with a focus on Brazil - Maria Cecilia Rivitti-Machado; Renata Ferreira Magalhães; Roberto Souto da Silva; Gleison V Duarte; Fabiana ZS Bosnich; Roberto Gaspar Tunala; Francisco José Forestiero (BioExcel Publishing Ltd, 2022)
Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease associated with a significant negative impact on the quality of life of patients. Methods: We conducted a systematic review to assess current treatment for HS, with a special focus on therapies approved or used in Brazil. We used the PICO framework to improve the research process. The systematic review was reported in line with the PRISMA statement checklist. The search was conducted with clinical questions on two global databases (PubMed (MEDLINE) and Google Scholar) and three databases especially selected to retrieve Brazilian outcomes (BVS, SCIELO and REDALYC). Results: Overall, 4640 articles were screened, 182 articles were analysed and 70 were used in a thematic qualitative analysis. Of these, 12 articles were from Brazil. The evidencebased literature was largely limited to case reports, case series, observational studies and expert opinion. Topical therapy, lifestyle interventions and oral antibiotics appeared as effective measures for mild HS. However, moderate-to-severe HS remains refractory to conventional treatments. Conclusion: Some biologic agents, such as adalimumab, infliximab, ustekinumab and secukinumab, have been shown to be effective in the management of moderate-to-severe HS that failed conventional treatment and demonstrated a good tolerability and safety profile.